(untitled) (Nigerian Journal of Pharmaceutical Research, 2024)
Background: The Coronavirus disease 2019 (COVID-19) pandemic has been a health issue of great concern. The disease has caused a substantial reduction in the workforce globally. In 2020, several vaccines were approved to prevent COVID-19 infection. Objective: This study evaluated adverse events following the administration of the COVID-19 vaccine among secondary healthcare workers in Kwara State, Nigeria Methods: This was a multicenter, and cross-sectional study conducted in eleven secondary healthcare hospitals among 348 health workers using a validated questionnaire. Ethical approval and informed consent were obtained appropriately. The questionnaire was read, explained, and distributed to the respondents at each facility between December 2022 and June 2023. The forms were filled out accordingly. Appropriate statistical software was used to analyze the collected data. Results: Among the 348 respondents studied, most were females (70.4%) within the age range of 31-40 years (50.3%). Few (16.4%) of the respondents were infected, however, the majority (62.9%) were fully vaccinated. Approximately one-third (31.1%) received the AstraZeneca vaccine. The most commonly experienced adverse events were fever (34.2%), headache (33.9%), tiredness (31.0%), and general body pain (30.3%). There was a significant association between the type of vaccine administered, dose received, and adverse events experienced at p < 0.05. In addition, there was a significant correlation between adverse events and the gender of the respondents at p < 0.05. Conclusion: Some respondents experienced adverse events after administration of COVID-19 vaccination. These events were associated with the type of vaccine, dose of vaccine received, and gender.